Scientific Approach Methodology Model of Thought/Theory of Imre Lakatos' Research Program - Durotul Qoyimah; Usman Usman (al-Afkar, Journal For Islamic Studies, 2026)
This article discusses the scientific thinking of Imre Lakatos, a Hungarian philosopher of science who combined important elements of Karl Popper's falsification theory and Thomas Kuhn's scientific paradigm, thus giving birth to the idea of a scientific research program methodology. In this framework, science is seen as a process of gradual theory evolution through a structured and dynamic research program. Lakatos emphasized that the development of science is not simply determined by a single piece of evidence that refutes an old theory, but rather through a series of theories developed based on strong basic principles. His research program model consists of three main elements, namely: (1) Hard core as a core principle that cannot be challenged, (2) Protective belt in the form of auxiliary hypotheses that can be modified to protect the core of the theory, and (3) Series of theories that show the continuity and development of theories in the research program. This approach is not only relevant in the natural and social sciences, but also makes a major contribution to the development of Islamic science. With an integrative approach, Lakatos' thinking is able to offer a strong, logical, and flexible philosophical framework to advance science in a multidisciplinary and transformative manner.